2014
DOI: 10.2147/clep.s72282
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis in Canadian children: a national analysis using administrative data

Abstract: BackgroundSevere infection resulting in sepsis is recognized as a leading cause of morbidity and mortality worldwide. The purpose of this study is to use longitudinal, population-based data to report national-level hospital metrics, providing a current assessment of the status of sepsis hospitalizations in Canadian children.MethodsWe performed an analysis of previously abstracted data from the Canadian Institute for Health Information (CIHI) Discharge Abstract Database (DAD). Children aged 0–17 years at the ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 33 publications
1
15
0
3
Order By: Relevance
“…Os dados da literatura apontam que a sepse pediátrica é uma doença bastante prevalente tanto em países desenvolvidos quanto em desenvolvimento, sendo que nestes últimos a sepse representa um problema médico, social e econômico mais grave 11,16,19,21,23,27,29,42,53,54,[56][57][58][59][60] . O aumento da frequência de sepse relacionada a infecções virais, observado em estudos recentes de sepse pediátrica, alerta para a importância de iniciativas que visem à redução da ocorrência e da disseminação de doenças infectocontagiosas, incluindo as virais.…”
Section: Análise Da Frequência De Sepse De Acordo Com O Nível De Deseunclassified
See 1 more Smart Citation
“…Os dados da literatura apontam que a sepse pediátrica é uma doença bastante prevalente tanto em países desenvolvidos quanto em desenvolvimento, sendo que nestes últimos a sepse representa um problema médico, social e econômico mais grave 11,16,19,21,23,27,29,42,53,54,[56][57][58][59][60] . O aumento da frequência de sepse relacionada a infecções virais, observado em estudos recentes de sepse pediátrica, alerta para a importância de iniciativas que visem à redução da ocorrência e da disseminação de doenças infectocontagiosas, incluindo as virais.…”
Section: Análise Da Frequência De Sepse De Acordo Com O Nível De Deseunclassified
“…Os resultados do presente estudo diferem daqueles estudos, uma vez que não foram observadas tais associações, seja no que se refere à mortalidade dos lactentes seja com relação ao gênero masculino. ,27,30,57,58 . No estudo de Typpo et al109 , a presença de DMOS durante as primeiras 24 horas de internação na UTIP aumentou 11 vezes a chance de óbito de crianças sépticas.…”
unclassified
“…Also using administrative data from hospital record systems, Thompson and Kissoon 22 reported that between 2004 and 2009, sepsis accounted for 4,000 hospital admissions of children and 200 deaths per year in Canada. Among children with sepsis, 22% had severe sepsis.…”
Section: Epidemiology Of Severe Sepsis and Septic Shock In Children Imentioning
confidence: 99%
“…The mortality from severe sepsis and septic shock in these countries remains high. [22][23][24][25] A study from Italy 23 reported a 51% mortality rate from septic shock, and 30.6% rate of early mortality (<24 hours). The high mortality from septic shock in Italian PICUs was attributed to the inadequate treatment of shock, because in the study period, none of the PICUs adopted the algorithm for severe sepsis and septic shock treatment in children proposed by American College of Critical Care Medicine -Pediatric Advanced Life Support.…”
Section: Epidemiology Of Severe Sepsis and Septic Shock In Children Imentioning
confidence: 99%
“…Mortality is highest in low-and middleincome countries (LMICs), with five million deaths annually, where poor socio-economic circumstances, limited access to care and non-resilient health systems result in worst outcomes (2). Recent estimates from the United States of America (USA), Canada, Australia, China, India and Europe showed a rising incidence and high mortality rates in children (2)(3)(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%